Genome-wide association studies reveal genomic regions and positional candidate genes for fat deposition in chickens - Moreira, Gabriel Costa Monteiro (2018)
Excess of fat deposition is a negative factor for poultry production, which affects feed efficiency and consequently the costs of meat production. The incorporation of genomic tools in poultry breeding programs may help to accelerate the selection for increased production efficiency. In this context, we genotyped approximately 2,000 42 days-old chickens from two different populations (Brazilian F2 Chicken Resource population and TT broiler Reference Population) using a high-density SNP array (600K, Affymetrix) to estimate genomic heritability of fatness-related traits, to identify genomic regions and positional candidate genes (PCGs) associated with these traits. We performed genome-wide association (GWAS) analysis using GenSel software (Bayesian approach) to identify 1 Mb genomic windows associated with abdominal fat, skin and carcass fat content traits. The search for PCGs were made within each genomic windows associated considering their Gene Ontology (GO) terms and also the literature information. We also integrated into this study NGS-SNPs data from both populations and selection signature regions identified in Brazilian F2 Chicken Resource population to refine the list of PCGs. The genomic heritability values for fatness-related traits were from moderate to high (greater than 0.30). We identified quantitative trait loci (QTL) for abdominal fat, skin and carcass fat content traits harboring several PCGs involved in biological processes of fat deposition. We identified several NGS-SNPs annotated in potential functional regions in our PCGs and some of those were predicted as deleterious and high impact mutations. Besides that, some genes overlapped with selection signature regions in Brazilian F2 Chicken Resource population. Important candidate genes for fat deposition were identified, providing new insights to achieve a better understanding of the genetic control of fat deposition in chickens.